What to make of makerspaces: Tools and DIY only or is there an interconnected information resources space?. Issue 4 (16th November 2015) - Fourie, Ina; Meyer, Anika
Abstract : Purpose: – Much has been published on makerspaces: the history, development and progress and how they are used – stories of successes and opinions on their potential. The purpose of this paper is to comment on such publications within the library and information science (LIS) literature and to warn libraries to not only focus on providing physical spaces and tools but to explore the bigger potential of extended, interconnected spaces for information and information resources and "mutations" of makerspaces such as makerlearning. Design/methodology/approach: – The contribution is based on a pragmatic and reflective analysis of the LIS literature on makerspaces. The questions are: what to make of the literature, and what needs to be done to enrich the subject literature to support an interconnected approach to makerspaces and information resources and information support? Findings: – There is a very strong focus in the literature on libraries as physical spaces for makerspaces, the planning, provision, maintenance and how-we-do-it approaches. Although very important this does not sufficiently explore an interconnection between makerspaces and an expanded information-related involvement of libraries, e.g. in information literacy training, guided inquiry, bridging the digital divide, research (embedded librarianship) and community support. Research limitations/implications: – There are many publications on makerspaces in the LIS literature. They however, mostly do not reflect on the opportunities to take a more holistic look at the potential of makerspaces in libraries interconnected to the use of information resources, and information-related support and intervention from libraries. Originality/value: – Although there are many papers on makerspaces the purpose of this contribution is to focus on extended input from libraries.